The dynamics of the economic efficiency indicators at Alba de Banat and Carpatina breeds - Rodica Chetroiu; Ion Calin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The paper presents the research results on the evolution of indicators of economic efficiency in the milk production at Alba de Banat and Carpatina breeds, for a period of 3 years, during 2012-2014, at S.C. AGROFAM HOLDING Feteðsti. Indicators studied are: average yield, total output value, total costs, unitary cost, variable costs, labor productivity in terms of value, costs for 1,000 lei main production, profit per unit of product, rate of return, breakeven point in physical and value units, rate of operational risk. Thus, their values are entirely superior for Alba de Banat goats, compared to Carpatina. Also, due to the downward curves of the milk production in the succession of the years studied, the levels of indicators are largely decreasing from year to year, with limits that support the efficiency of production activity.
Keywords: 330; milk; goats; indicators; efficiency